RESISTANCE OF POPCORN HYBRIDS TO Exserohilum turcicum, CAUSAL AGENT OF NORTHERN LEAF BLIGHT OF MAIZE - VIEIRA, Rafael Augusto; TESSMANN, Dauri José; HATA, Fernando Teruhiko; SOUTO, Eliezer Rodrigues; MESQUINI, Renata Moreschi (Scientia Agraria, 2009)
For evaluating resistance of experimental and commercial popcorn hybrids to Exserohilum turcicum, the causal agent of Northern leaf blight of maize, an experiment was carried out in randomized block design with four replications, in Maringá, State of Paraná, during the 2007/2008 cropping season. An additional objective was to compare the efficiency of using a single disease assessment compared to several assessments for discriminating resistance. The incidence and severity of the disease, evaluated four times during the season, were used for estimating the area under the disease progress curve of incidence (AUDPCI) and severity (AUDPCS). The last assessment of incidence and severity, AUDPCI and AUDPCS were used to compare the genotypes by analysis of variance and Scott-Knott test. Spearman’s rank correlations among incidence, severity, AUDPCI and AUDPCS values were estimated to describe their associations. Significant differences (P≤0.001) of resistance were verified among genotypes. The hybrids UEM129, UEM145, UEM140, UEM116 and UEM101 presented the lowest levels of disease and were considered the most resistance genotypes. These genotypes overcame UEM109, UEM153 and IAC 112, which are considered resistant standards and, Zélia and Jade, considered susceptible. The correlation analysis showed that the assessment of incidence and severity at dough stage did not provide same data as AUDPCI and AUDPCI for discriminating resistance to E. turcicum.